IL-6 from cerebrospinal fluid causes widespread pain via STAT3-mediated astrocytosis in chronic constriction injury of the infraorbital nerve - Ning Yu; Huan Cui; Sixuan Jin; Penghao Liu; Yehong Fang; Fengrun Sun; Yan Cao; Bo Yuan; Yikuan Xie; Wanru Duan; Chao Ma (Journal of Neuroinflammation, 2024)
Abstract Background The spinal inflammatory signal often spreads to distant segments, accompanied by widespread pain symptom under neuropathological conditions. Multiple cytokines are released into the cerebrospinal fluid (CSF), potentially inducing the activation of an inflammatory cascade at remote segments through CSF flow. However, the detailed alteration of CSF in neuropathic pain and its specific role in widespread pain remain obscure. Methods A chronic constriction injury of the infraorbital nerve (CCI-ION) model was constructed, and pain-related behavior was observed on the 7th, 14th, 21st, and 28th days post surgery, in both vibrissa pads and hind paws. CSF from CCI-ION rats was transplanted to naïve rats through intracisternal injection, and thermal and mechanical allodynia were measured in hind paws. The alteration of inflammatory cytokines in CCI-ION’s CSF was detected using an antibody array and bioinformatic analysis. Pharmacological intervention targeting the changed cytokine in the CSF and downstream signaling was performed to evaluate its role in widespread pain. Results CCI-ION induced local pain in vibrissa pads together with widespread pain in hind paws. CCI-ION’s CSF transplantation, compared with sham CSF, contributed to vibrissa pad pain and hind paw pain in recipient rats. Among the measured cytokines, interleukin-6 (IL-6) and leptin were increased in CCI-ION’s CSF, while interleukin-13 (IL-13) was significantly reduced. Furthermore, the concentration of CSF IL-6 was correlated with nerve injury extent, which gated the occurrence of widespread pain. Both astrocytes and microglia were increased in remote segments of the CCI-ION model, while the inhibition of astrocytes in remote segments, but not microglia, significantly alleviated widespread pain. Mechanically, astroglial signal transducer and activator of transcription 3 (STAT3) in remote segments were activated by CSF IL-6, the inhibition of which significantly mitigated widespread pain in CCI-ION. Conclusion IL-6 was induced in the CSF of the CCI-ION model, triggering widespread pain via activating astrocyte STAT3 signal in remote segments. Therapies targeting IL-6/STAT3 signaling might serve as a promising strategy for the widespread pain symptom under neuropathological conditions. Graphical abstract